Kecerdasan Emosional Dan Coping Caregiver Pada Pasien Stroke Hemoragik DI RSUD Soediran Mangun Sumarso Wonogiri - Kristna Adi Nugraha; Ros Endah Happy Patriyani (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Caregiver, Coping, Emotional Intelligence. Stroke acute attack caused physical disability and mental disability. The state will required caregiver assistance. Stroke patients will require treatment time is long enough so that will make the caregiver feel bored and empathy will be reduced. Bored in a long time will cause disturbed emotional. The Purpose of Research to investigate the relationship between emotional intelligence and coping caregivers for patients with hemorrhagic stroke in RSUD Soediran Mangun Sumarso Wonogiri. This research used correlation description with cross-sectional. The Research Subject were caregivers for patients with hemorrhagic stroke in RSUD Soediran Mangun Sumarso Wonogiri. Research carried out for a month. Sampling technique used total sampling and obtained 68 respondents. Research instruments used questionnaries. The result of emotional intelligence (73,5%) and coping (82,4%) in a good result. Spearman Rho test showed relationship between emotional intelligence and coping, significance level 0,042 and corellation 0,247. Low relation between emotional intelligence with coping caregivers for patients with hemorrhagic stroke in RSUD Soediran Mangun Sumarso Wonogiri. The next research, expected to add variable about characteristics of caregiver that affect the emotional intelligence and coping.